Sputum induction for the diagnosis of pulmonary tuberculosis in infants and young children in an urban setting in South Africa. Issue 4 (1st April 2000) - Zar, H J; Tannenbaum, E; Apolles, P; Roux, P; Hanslo, D; Hussey, G
Abstract : BACKGROUND: Bacteriological confirmation of pulmonary tuberculosis is difficult in infants and young children. In adults and older children, sputum induction has been successfully used; this technique has not been tested in younger children. AIMS: To investigate whether sputum induction can be successfully performed in infants and young children and to determine the utility of induced sputum compared to gastric lavage (GL) for the diagnosis of pulmonary tuberculosis in HIV infected and uninfected children. SUBJECTS AND METHODS: 149 children (median age 9 months) admitted to hospital with acute pneumonia who were known to be HIV infected, suspected to have HIV infection, or required intensive care unit support. Sputum induction was performed on enrolment. Early morning GL was performed after a minimum four hour fast. Induced sputum and stomach contents were stained for acid fast bacilli and cultured for Mycobacterium tuberculosis . RESULTS: Sputum induction was successfully performed in 142 of 149 children. M tuberculosis, cultured in 16 children, grew from induced sputum in 15. GL, performed in 142 children, was positive in nine; in eight of these M tuberculosis also grew from induced sputum. The difference between yields from induced sputum compared to GL was 4.3% (p = 0.08). M tuberculosis was cultured in 10 of 100 HIV infected children compared to six of 42 HIV uninfected children (p = 0.46). CONCLUSION: Sputum induction can be safely and effectively performed in infants and young children. Induced sputum provides a satisfactory and more convenient specimen for bacteriological confirmation of pulmonary tuberculosis in HIV infected and uninfected children.